2011
DOI: 10.1111/j.1398-9995.2011.02570.x
|View full text |Cite
|
Sign up to set email alerts
|

Basophil recruitment and activation in inflammatory skin diseases

Abstract: Basophils infiltrate into skin lesions more commonly than previously thought, and thus they may play important roles in a variety of inflammatory skin diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
235
1
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(260 citation statements)
references
References 35 publications
11
235
1
13
Order By: Relevance
“…45 Most notably, the skin lesions found in these diseases are histologically characterized by a marked basophil infiltration. 46 Thus, basophil-derived PGD2 may at least partly contribute to the pathogenesis of these inflammatory skin reactions.…”
Section: Discussionmentioning
confidence: 99%
“…45 Most notably, the skin lesions found in these diseases are histologically characterized by a marked basophil infiltration. 46 Thus, basophil-derived PGD2 may at least partly contribute to the pathogenesis of these inflammatory skin reactions.…”
Section: Discussionmentioning
confidence: 99%
“…This study also provided evidence that basophils are indispensable key players that link urticarial and papulonodular skin reactions. The fact that a number of basophils are present in long-lasting urticarial lesions and prurigo in humans (15) suggests that basophils, but not mast cells or T cells, play a major role in the pathogenesis of these diseases. One of the major and troublesome symptoms of prurigo is itching.…”
Section: Discussionmentioning
confidence: 99%
“…Prurigo lesions are histopathologically characterized by lymphocyte and eosinophil infiltration, with dermal edema and/or exudates. In addition, our recent findings revealed that prurigo is a disease involving prominent basophil infiltration (15). Basophils principally reside in the blood rather than peripheral tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A cell type that was brought into focus of allergy research is basophils. Immunohistochemistry using a novel human-specific anti-basogranulin antibody (BB1) revealed basophil infiltration in lesional skin suggesting an active pathogenic role in AD (102).…”
Section: Innate Immune Cells Involved In Admentioning
confidence: 99%